The EU, Irish Defence Forces and Contemporary Security
XXV, 443 p. 8 illus., 7 illus. in color.
Keywords: “This book is a critical and insightful contribution to the debate on Irish defence and the role of the Defence Forces.” — Ben Tonra, Professor, MRIA, The School of Politics and International Relations (SPIRe), University College Dublin, Ireland “By mainly examining Ireland’s defence policy and the Irish Armed Forces, this edited volume provides valuable knowledge to both practitioners and scholars. Undoubtedly, any reader interested in international relations and/or security studies, and especially those focusing on small states studies and/or comparative strategy, will gain new insights by exploring this book.” — Håkan Edström, Associate Professor in Political Science, Swedish Defence University, Sweden. This book aids any researcher, policymakers and military personnel in researching small states and militaries, European defence and security policy, as well as contemporary and emerging threats. This edited collection gathers academic commentators on Irish defence policy, military leaders from across the service components of the Irish Defence Forces and European defence experts to contribute to the first in-depth conversation and analysis on modern Irish defence and its application within the European Union. The aim of this edited book is to ascertain what capabilities are robust, which are lacking, what future threats need to be catered for, and what action is needed to ensure those threats will be addressed going forward. This book will explore emerging issues and applications of modern and contemporary threats within the context of Ireland, Europe and Western institutions. We have invited submissions from scholars, commentators, policymakers and military practitioners to evaluate the Irish Defence Forces and to illustrate the complexities facing small nations in formulating and resourcing defence and national security policy. Jonathan Carroll is a PhD Candidate in Military History at Texas A&M University, USA. Matthew G. O’Neill is a Leverhulme Interdisciplinary Network on Cybersecurity and Society (LINCS) postgraduate researcher in Political Science at the Senator George J. Mitchell Institute for Global Peace, Security and Justice at Queen’s University Belfast, UK. Mark Williams is a Leverhulme Interdisciplinary Network on Cybersecurity and Society (LINCS) postgraduate researcher at the Senator George J. Mitchell Institute for Global Peace, Security and Justice at Queen’s University Belfast, UK.